Multicriteria method as a tool to aid in the decision on alternative transport use - Toreta Braz; Chiquieri, Julien; Gonçalves, Wellington (Brazilian Journal of Production Engineering, 2020)
The economic situation experienced in Brazil has imposed on public and private organizations the need to improve their processes in the search for efficiency in the use of resources. In this context, it is still necessary to search for solutions for transporting passengers and cargo that consider the desire of individuals regarding existing alternatives. The purpose of this article is to raise the priorities of users, select and prioritize alternatives for the model of cargo and passenger transport services in an institution. The Multicriteria Analytic Hierarchy Process (AHP) method was used because it allows the participation of several subjects, and in many cases the criteria created by them are conflicting. The results achieved demonstrate that the logistical and economic factors stand out in the preference of the user audience, reaching respectively 59.80% and 22.90%, and that the best alternative points in the direction of total outsourcing of the service. The suggested approach promotes greater knowledge of the customer by the organization and provides the possibility of creating strategies for the provision of transport services from the user’s perspective.